PENGARUH TINGKAT FINANCIAL LITERACY DAN FAKTOR SOSIODEMOGRAFI TERHADAP PERILAKU KEPUTUSAN INVESTASI INDIVIDU - Rasuma Putri, Ni Made Dwiyana; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study is to explain the influence level of financial literacy and sociodemographic factors on behavior of individual investment. Respondents are unmarried employees in Denpasar with a sample of 83 peoples. Determination of sample using non-probability sampling with accidental sampling approach.Data were analyzed by using Multiple Linear Regression Analysis. The results of this study indicate that the level of financial literacy has a positive effect on the behavior of individual investment decisions, whereas the differences in influence between men and women on the behavior of individual investment decisions and income negatively affect the behavior of individual investment decisions. Based on the results of statistical data financial literacy variables have the greatest influence in determining the behavior of individual investment decisions compared with sociodemographic factors. This explains that a person's knowledge of managing his personal finances is a key factor in determining an investment decision.